PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA PADA MEDIUM SUB SOIL ULTISOL YANG DIBERI ASAM HUMAT DAN KOMPOS TANDAN KOSONG KELAPA SAWIT - JANRICO VALENTINO SEMBIRING; NELVIA NELVIA; ARNIS EN YULIA (Jurnal Agroteknologi, 2015)
Ultisol have low fertility, the sub soil of ultisol have fertility and organic matter content are very low. Compost of oil palm empty fruit bunches (OPEFB) and humic acid are useful improving fertility and organic matter content so that it can support growth of the plant. The research aims to study the effect of application of compost OPEFB and humic acid on sub soil ultisol to growth of the oil palm seedling’s in the main nursery. The experiment was conducted at the Experimental Farm of the Faculty of Agriculture, University of Riau, Pekanbaru. The experiment were carried out in the form of factorial with a completely randomized design. The first factor is compost of OPEFB that consists of 4 levels (0, 25, 50 and 75 g/polybag) and as the second factor is the humic acid that consists of 3 level (0, 25 and 50 g/polybag). The parameters observed were statistically analyzed using analysis of variance, followed by Duncan’s multiple range test at 5%.The parameters measured were plant height, in the number of leaves, the increase in diameter stump, root crown ratio, dry seedling weight. The results slowed that the application of compost of OPEFB 25-75 g/polybag followed by humic acid 25, 50 g/polybag significantly increased plant height, in the number of leaves, the increase in diameter stump, root crown ratio, dry seedling weight composed than without compost OPEFB and humic acid, but now significantly with the other combination action.